THEORETICAL FOUNDATIONS OF TEACHING CHILDREN TO MONOLOGICAL SPEECH - Bazarbayevna, Rimbayeva Ozoda (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
this article provides a number of information and feedback on the theoretical foundations of teaching children to monological speech and on monological speech